2000
DOI: 10.1115/1.1333694
|View full text |Cite
|
Sign up to set email alerts
|

Local Heat Transfer and Flow Structure on and Above a Dimpled Surface in a Channel

Abstract: Experimental results, measured on and above a dimpled test surface placed on one wall of a channel, are given for Reynolds numbers from 1250 to 61,500 and ratios of air inlet stagnation temperature to surface temperature ranging from 0.68 to 0.94. These include flow visualizations, surveys of time-averaged total pressure and streamwise velocity, and spatially resolved local Nusselt numbers, which are measured using infrared thermography, used in conjunction with energy balances, thermocouples, and in situ cali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
81
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(91 citation statements)
references
References 11 publications
4
81
0
Order By: Relevance
“…Case [8].It can also be seen that the variation in the Nusselt number is gradual with Reynolds number as expected [14,15]. It can be seen that 'Nu' increases as 'Re' increases in all the three cases.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…Case [8].It can also be seen that the variation in the Nusselt number is gradual with Reynolds number as expected [14,15]. It can be seen that 'Nu' increases as 'Re' increases in all the three cases.…”
Section: Resultssupporting
confidence: 57%
“…They observed a considerable increase in the distribution of local heat transfer coefficient everywhere on these dimple surfaces as compared to flat surface. Mahmood et al [8], experimentally investigated the effect of dimples on heat transfer augmentation .They used the flow visualization techniques and concluded that the periodic nature of shedding off of vortices is the main cause of enhancement of heat transfer and is much more pronounced at the downstream rims of the dimples. Xie et al [9] numerically investigated the heat transfer and fluid flow characteristics of teardrop dimple along with teardrop protrusion having different eccentricities.…”
Section: Introductionmentioning
confidence: 99%
“…The different arrangements of dimples used are [1,11]. The formation of vortex pairs, periodically shedding off from the dimples at low angles, a large up wash regions with some fluids coming out from the central regions of the dimples, are the main causes of enhancement of Nusselt number [6].This happens mostly at low angle orientation of dimples (30 0 ), as at low angles the dimples are very close to each other so a pronounce effect of dimples is felt. It can also be seen that the variation in the Nusselt number is almost gradual with orientation as expected [12,13].…”
Section: Resultsmentioning
confidence: 99%
“…They observed a considerable increment in the heat transfer rate for the surfaces having dimples (About 2.5 times then their smooth surfaces). Mahmood et al [6] conducted an experiment to investigate the effect of dimples on heat transfer using the flow visualization techniques and concluded that the periodic nature of shedding off of vortices is the main cause of enhancement of heat transfer (much more pronounced at the downstream rims of the dimples). Mahmood et al [7] conducted an experiment to study the effect of Reynolds number, aspect ratio, and temperature ratio in a channel with dimples.…”
Section: Introductionmentioning
confidence: 99%
“…Afanasyev [35] used spherical cavities as the vortex generator and got heat transfer enhancement of 30-40% with air as the working fluid. Mahmood [36] also tried to use dimpled channel to enhance the heat transfer but obtained a very less increase in heat transfer and pressure drop as no form drag was produced by the protruding objects. …”
Section: E Other Passive Techniquesmentioning
confidence: 99%